A young merchant navy officer with night sweats, fever, and weight loss - Pesce, Antonio; Magro, Gaetano; Puleo, Stefano (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Pesce A, Magro G, Puleo S. A young merchant navy officer with night sweats, fever, and weight loss. Turk J Gastroenterol 2019; 30(11): 988-90.